Detection of fundic varices obturation by endoscopic ultrasound versus multidetector computed tomography - Amr Elrabat; Salah El-Gamal; Mohammad M Kashwaa; Mohamed M El-Rakhawy (SpringerOpen, 2019)
Background Gastroesophageal varices (GVs) present in 50% of patients with liver cirrhosis. GVs bleed at a rate of 5-15%, and the 6-week mortality after hemorrhage is 20%. GVs are treated with a tissue adhesive, cyanoacrylate, where repeated sessions are performed 2-4 weeks until obliteration, and eradication is achieved with 2-4 injections using 1-2 ml/ session. Endoscopic ultrasonography (EUS) was found superior to endoscopy in detecting gastric varices. Gastric varices obturation can be detected using CD-EUS to assess blood flow in variceal lumen after cyanoacrylate injection. Multidetector computed tomography (MDCT) is an acceptable imaging modality for abdominal vascular system and assessment of endoscopic therapy of fundal varices. To our knowledge, there is no study for detecting GV obturation yet. The aim of this study to compare between EUS and MDCT in detecting obturation of GV and comparing EUS and upper endoscopy in detection of GV obturation. Patients and methods A total of 22 patients with liver cirrhosis presented with acute GV bleeding for the first time, which was confirmed and managed by upper endoscopy, being carried out in the first 12 h after admission. Then the patients were subjected to monthly gastric varices injection of cyanoacrylate until they appeared to be obturated by upper endoscopy using blunt end of injection catheter sheath to palpate varices. After that EUS and CT were done for evaluation of GV, in addition to perigastric and paragastric collaterals. Results EUS is superior to CT in detecting GV obliteration, with a high significant difference (P=0.04), whereas EUS and upper endoscopy have similar results in detecting the obliteration of GV (P=0.68). There was a statistically significant association between splenic size and GV obliteration (P=0.002) and a significant negative correlation between size of paragastric collaterals and GV obturation. Conclusion EUS is superior to CT in detecting the obliteration of GV.